Advances in design engineering and merits of electron transporting layers in perovskite solar cells. Issue 9 (8th July 2020) - Pan, Han; Zhao, Xiaojuan; Gong, Xiu; Li, Hao; Ladi, Najib Haji; Zhang, Xiao Li; Huang, Wenchao; Ahmad, Shahzada; Ding, Liming; Shen, Yan; Wang, Mingkui; Fu, Yongqing
Abstract : The electron transport layer plays an essential part for high-performing perovskite solar cells, on which successful extraction of charges from light harvester and the transfer to the electrode are critically dependent. Abstract : The emerging photovoltaic technology, namely perovskite photovoltaics, follows a style to the blooming flower with superficial prosperity described by the ancient poet Yuxi Liu. Metal-halide perovskite has become one of the most promising photovoltaic materials for thin-film solar-cell applications, mainly due to its exellent visible light capture capability, large diffusion coefficients and long diffusion lengths of charge carriers (both electrons and holes). The reported power conversion efficiency of laboratory produced perovskite solar cells (PSCs) has exceeded 25%. However, this value was only achieved for devices of less than 0.1 cm 2 dimensions, and decreases significantly with the increase in area (for example, down to 11.6% for a device area of ∼800 cm 2, showing the issues with the scalability). In PSCs, the electron transport layer (ETL) has to perform two essential functions, which are related: (i) to collect and transfer charges after the injection of electrons from the perovskite light harvester; and (ii) to block the backflow of holes, thus realizing effective charge separation and suppressing charge carrier recombination. However, there are several critical issues associated with the ETLs which limit the further development of the PSCs. For example, the experimentally obtained open-circuit voltages in PSCs are typically much lower compared to the theoretical voltage limit with their optical bandgaps between 1.59 and 1.63 eV. This is mainly attributed to inefficient charge transport in the PSCs due to inhomogeneous charge accumulation and serious interfacial recombination at the interfaces between the ETL and the perovskite active layer. We scan recent developments of ETLs in PSCs, and discuss design methodologies, mechanisms, processing and characterization of new types of ETLs. High power conversion efficiency with large open-circuit voltages/photo-currents could be achieved through designing materials and microstructures for high-quality ETLs with a high electron mobility, high electrical conductivity and pinhole-free film morphology. It is crucial to balance the charge diffusion processes in the respective charge collective layers of PSCs as the interfaces between the ETLs and perovskites along with their interfacial structures play key roles in achieving new solid-state mesoscopic solar cells optimized open circuit voltages and output photocurrents.